Event-Triggered Control for LPV Modeling of DC-DC Boost Converter - Soni, Sandeep Kumar; Singh, Saumya; Singh, Kumar Abhishek; Xiong, Xiaogang; Saket, R.K.; Sachan, Ankit (Institute of Electrical and Electronics Engineers Inc., 2023)
This brief presents the event-triggered control (ETC) for linear parameter varying (LPV) model of boost converters. We examine the nonlinear dynamics of boost converters in the LPV framework. The proposed controller is duty-ratio-dependent and provides better performance while requiring less computation. Using the parameter-dependent Lyapunov function (PDLF), we demonstrate the stability analysis of the proposed approach. Furthermore, we demonstrate that the inter-event time is lower bound by a positive constant, which indicates Zeno behavior free performance. In comparison to earlier time-invariant synthesis techniques, the LPV formulation offers for increased robustness and performance properties. Simulation and experimental results validate the effectiveness of the proposed method.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: boost converter; ETC; Linear parameter-varying systems; parameter dependent Lyapunov function